KUALITAS INFORMASI POLITIK DAN RELASINYA DALAM DEMOKRASI DI LEVEL LOKAL - Arif Akbar Jatmika Putra; Muharjono Muharjono (Jurusan Ilmu Hubungan Internasional, 2016)
Information is very essential to build human rationality to act. This is also occurred in the political world. Information becomes preferences and aggregate for all of citizen for do their political activities. Thus, political information which disseminates over the citizens through information public canal need to preserve it is quality, particularly for political information that produced or being distributed by the press. The press has their responsibilities toward values which conducted in elements of journalism. Also, the press has their highest responsibilities to public. Meanwhile, for citizens who are seldom interacting with the political parties and other activities that related to politics, they only have press as sources of their political information. The qualified political information is input for citizens to correctly to vote during the elections. Indeed, there are many factors which affect voting behaviour, despite of political information. But, to create political discourse over the citizens, most of only can be done by the qualified political information. Which is, better for increasing voting correctness for citizens.